Heritage literacy as the mission - responsibility of museums and educational institutions - Babić, Darko muzeolog (2009)
The idea, and the term heritage literacy tend to transcend functions museum and heritage professionals are constantly devoted to, applied to whole communities they (i.e. institutions) embrace. The term itself goes beyond visitors' analysis anticipating eco-museums ideas. It could be anchored within communication, but more precisely it is specific interpretation process reachable via different activities. Thus the heritage literacy is a desirable and expected outcome of the heritage based education process. It has foundation in the comprehension of literacy as a state of having knowledge or competences in an explicit field and at the same time in comprehension of the heritage as a collective capital of (any) community. Still, it uttermost goal always tends more toward sensitiveness then formal acquiring of the data or knowledge. The possible way toward realisation of the heritage literacy will be demonstrated by on-going project run by the University of Zagreb in Ravni kotari region, one of Croatian ex-war areas. Having as a base multiethnic community coping sometimes with essential living conditions, in vicinity of developed coastal (tourist) zone initiated project has the core idea that local, common heritage could be the main catalyst of their development, and prosperity of the entire region.